Study on the user's satisfaction towards library services at Penang Public Library Cooperation (PPLC) / Noorazreen Laily Awang Yak - Awang Yak, Noorazreen Laily (2011)
Changes in today's technology make it necessary for library administrative to look anew the role, mission and the future of the public library. A public library is an organization established, supported, and funded by the community, either through local, regional or national government. It provides access to knowledge, information and works of the imagination through a range of resources and services. It is equally available to all members of the community regardless of race, nationality, age, gender, religion, language, disability, economic, and employment status and educational attainment. The main aim of this study is investigated about those elements which are contributed for the user's satisfaction towards library services at Public Ubrary. This study is targeted on the Penang Public Library Corporation. Its generally involves by the random users or membership at Penang Public Library Corporation. The factors which are contribute in measuring the user's satisfaction towards library services are availability of library services such as library facilities and library activities, accessibility of library collections or resources, level of customer service and Information Technology developments. The primary purpose of public library is to provide resources and services in a variety of media to meet the needs of their members. They have an important role in the development and maintenance of a democratic society by giving the individual access to a wide and varied range of knowledge, ideas, and opinions. This paper also suggests that for any reliable library effectiveness study, all factors associated with user satisfaction should be investigated together.